Netizens' Language Politeness In The 2024 Presidential Debate Comments Column On Youtube Media - Mukhtar, Ruyatul Hilal; Ibrahim, Anwar (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to describe (1) the use of the principles of politeness in language (2) violations of the principles of politeness in language committed by netizens in "This is the focus of netizens in the first debate of the 2024 presidential candidates" on Kompas Tv. In this research, researchers used a descriptive-qualitative research design. The subject of this research is the speech of netizens in the comment’s column of YouTube media. This research uses Leech's theory of politeness, namely the maxim of wisdom, the maxim of acceptance, the maxim of generosity, the maxim of humility, the maxim of suitability, and the maxim of sympathy. The data was collected using the listening method and followed by an advanced technique: the note-taking technique. Researchers found uses and violations of politeness principles. The results of this research are as follows. (1) the use of politeness principles in the research found, namely, the maxim of wisdom, the maxim of acceptance/suitability, the maxim of humility, and sympathy. (2) violations of the principles of politeness found, namely, violations of the maxim of wisdom, the maxim of acceptance/suitability, the maxim of humility, and sympathy.